Financial Application for the STMIK Mardira Indonesia Educational Institution - Zelani, Fajar Habib; Sudarsono, Nono; Putera, Yuda Purnama; Solihin, Solihin (Journal of Economics, Management, and Entrepreneurship, 2024)
The waqf asset management system is essential for maximizing and optimizing the managed assets to achieve the highest and most favorable outcomes. A professional waqf institution in Bandung possesses waqf assets dispersed throughout several regions in Indonesia, and its management has successfully reached the level of optimizing productive waqf. Nevertheless, waqf assets are managed manually, leading to slower and worse management practices. This research aims to address the issue of managing waqf assets by applying ISO 55001 to the waqf asset management system in a selected professional waqf institution in Bandung. The research approach employs descriptive analysis with the Object-Oriented Software Engineering (OOSE) system development process. The results reveal eight functions based on 8 and 9 criteria that should be present in the asset management system according to ISO 55001. The program incorporates these eight functionalities and achieves a System Usability Scale (SUS) score of 84.6, signifying a B grade and outstanding acceptance. The ISO 55001 certification readiness level is 57.14%, as determined by the ISO 55001 Self-assessment conducted by the British Standard Institute (BSI). The researcher utilized Black Box testing to evaluate the program's functionality, and the findings indicate that all operations are functioning as anticipated.